2023
DOI: 10.1186/s40793-023-00494-w
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome of solitary bees is mainly affected by pathogen assemblage and partially by land use

Abstract: Pollinators, including solitary bees, are drastically declining worldwide. Among the factors contributing to this decline, bee pathogens and different land uses are of relevance. The link between the gut microbiome composition and host health has been recently studied for social pollinators (e.g. honeybees), whereas the information related to solitary bees is sparse. This work aimed at the characterization of the gut microbiome of the solitary bees Xylocopa augusti, Eucera fervens and Lasioglossum and attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 89 publications
0
7
1
Order By: Relevance
“…However, in a study, Pseudomonads in solitary bees were the most represented bacteria, with Lasioglossium, Xylocopa augusti, and Eucera fervens being prevalent in the gut microbiome, with average relative abundances of 39.84%, 36.05%, and 50.91%, respectively [128].…”
Section: Contribution Of Pseudomonads To Bee Well-being and The Biolo...mentioning
confidence: 96%
See 1 more Smart Citation
“…However, in a study, Pseudomonads in solitary bees were the most represented bacteria, with Lasioglossium, Xylocopa augusti, and Eucera fervens being prevalent in the gut microbiome, with average relative abundances of 39.84%, 36.05%, and 50.91%, respectively [128].…”
Section: Contribution Of Pseudomonads To Bee Well-being and The Biolo...mentioning
confidence: 96%
“…It has been shown that the gut bacteria Serratia and Pseudomonas contribute to atrazine (herbicide) degradation. Both of these bacteria have atrazine-degradation-related genes, which conferred resistance in an experimentally exposed wasp population [128,142]. The genes and corresponding enzymes involved in atrazine degradation by a Pseudomonas sp.…”
Section: Contribution Of Pseudomonads To Bee Well-being and The Biolo...mentioning
confidence: 99%
“…This principle applies well to social insect species, which possess highly conserved and vertically transmitted microbiome compositions [ 86 , 87 ] . However, the theory fails to consider solitary insect microbiomes, which more often mimic the composition of their environment [ 6 , 88 ] . Other researchers have argued that the level of connectedness determines the health of the microbiome, rather than the balance of species [ 84 ] .…”
Section: Insect Gut Cell Lines Have the Potential To Address Microbio...mentioning
confidence: 99%
“…Regarding the microbiota of solitary bees, this is an entirely diverse topic and is a factor modulating host health and development. De Landa et al [ 47 ] reported that the gut microbiome of solitary bees ( Xylocopa augusti , Eucera fervens , and Lasioglossum spp.) is associated with the presence of species such as Pseudomonas as the major core taxa in all species analyzed, whereas other, such as lactobacilli, Spiroplasma , and Sodalis , were the second most abundant taxa.…”
Section: Other Bee Species Microbiotamentioning
confidence: 99%